2010
DOI: 10.1096/fj.09-144592
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the human biliverdin reductase gene structure and regulatory elements: promoter activity is enhanced by hypoxia and suppressed by TNF‐α‐activated NF‐κB

Abstract: hBVR is a Ser/Thr/Tyr kinase/scaffold protein/transcription factor/intracellular transporter of regulators. hBVR is an upstream activator of the insulin/IGF-1/MAPK/PI3K signaling pathway, and of NF-kappaB. As a reductase, it converts biliverdin to the antioxidant, bilirubin. hBVR gene has 8 exons; exon 1 is not translated. We report the characterization of hBVR promoter and its negative and positive regulation, respectively, by TNF-alpha and hypoxia. The 5' end of exon 1 was defined by primer extension analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 74 publications
3
18
0
Order By: Relevance
“…Accordingly, inhibition of UV-irradiation induced inflammatory cytokines secretion is important to protect skin from photo-damage. Recently, several studies have shown that BVD is rapidly converted by BVR to bilirubin, resulting in decreased release of proinflammatory cytokines, such as IL-12, IL-6, and TNF-a in animals [44]. In the present study, the proinflammatory cytokine IL-6 increased in the UVB group, and BVD treatment diminished IL-6 expression, thereby preventing the skin inflammation mediated by UVB-induced oxidative stress.…”
Section: Discussionsupporting
confidence: 61%
“…Accordingly, inhibition of UV-irradiation induced inflammatory cytokines secretion is important to protect skin from photo-damage. Recently, several studies have shown that BVD is rapidly converted by BVR to bilirubin, resulting in decreased release of proinflammatory cytokines, such as IL-12, IL-6, and TNF-a in animals [44]. In the present study, the proinflammatory cytokine IL-6 increased in the UVB group, and BVD treatment diminished IL-6 expression, thereby preventing the skin inflammation mediated by UVB-induced oxidative stress.…”
Section: Discussionsupporting
confidence: 61%
“…pro-inflammatory and pro-proliferative targets (Gibbs et al, 2010). Consistent with the possibility that BVR regulates the activity of NFκB, TNF--mediated stimulation caused NFκB to act as a repressor of BVR expression which demonstrates that BVR is competitive with the inflammation process mediated by TNF-through activation of NFκB.…”
Section: Pharmacology 556supporting
confidence: 59%
“…When BVR was over-expressed in HEK 293 and MCF-7 cells, the cells were arrested in G 1 /G o stage . Furthermore, over-expression of BVR also protected cells from NFκB-mediated proliferation after stimulation with TNF- (Gibbs et al, 2010). These findings are consistent with a number of studies that have used various cell types (HEK293 (Miralem et al, 2005), HeLa (Ahmad et al, 2002), cardiomyocytes (Pachori et al, 2007) and renal epithelial cells (Young et al, 2009)) to show that the inhibition of BVR expression using interference RNA resulted in apoptosis after the cells were challenged with arsenite, hydrogen peroxide, hypoxia/reoxygenation, and angiotensin II, respectively.…”
Section: Pharmacology 554mentioning
confidence: 93%
“…For example, both rat and human BVRa gene promoters contain regulatory elements for NFκB and HIF-1α (Gibbs et al ., 2010) which is in agreement with human BVRa being activated by hypoxia (Salim et al ., 2001) and inhibited by NFκB (Gibbs et al ., 2010). These results are consistent with the observation of four HRE motifs in the proximal promoter region of the zebrafish bvra gene (Figure 11).…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with the observation of four HRE motifs in the proximal promoter region of the zebrafish bvra gene (Figure 11). Additionally, computer analysis of the human BVRa promoter suggested numerous candidate regulatory elements including the aryl hydrocarbon receptor (AHR) and heat shock factor 1 (HSF-1) (Gibbs et al , 2010). Interestingly, both bilirubin and biliverdin have also been implicated in the activation of the AHR pathway (Sinal and Bend, 1997; Phelan et al ., 1998).…”
Section: Discussionmentioning
confidence: 99%